Cinephilia movies, love and memory - Valck, Marijke de 1975-; Hagener, Malte 1971- (Film culture in transition, 2005)
They obsess over the nuances of a Douglas Sirk or Ingmar Bergman film; they revel in books such as Franois Truffaut's Hitchcock; they happily subscribe to the Sundance Channel-they are the rare breed known as cinephiles. Though much has been made of the classic era of cinephilia from the 1950s to the 1970s, Cinephilia documents the latest generation of cinephiles and their use of new technologies. With the advent of home theaters, digital recording devices, online film communities, cinephiles today pursue their dedication to film outside of institutional settings. A radical new history of film culture, Cinephilia breaks new ground for students and scholars alike